Projeto basquetebol sobre rodas da FCT/UNESP - Brancatti, Paulo Roberto [UNESP] (2015)
Basketball on wheels is a sport practiced by people with physical deficiency. To teach or work with that modality, the teacher of Physical Education requires some basic knowledge that includes the understanding about the proper modality and its differences compared to conventional basketball and functional classification of athletes or even, about the wheelchair used in sports. Thus, the project aims to present its development through the practice of the modality in relation to the participants of the same.